2022
DOI: 10.1186/s40001-022-00661-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of high-flow nasal cannula during sedated digestive endoscopy: a systematic review and meta-analysis

Abstract: Background Studies evaluating the role of high-flow nasal cannula (HFNC) in sedated digestive endoscopy have reported conflicting results. This meta-analysis evaluates the effectiveness of HFNC in patients undergoing digestive endoscopy procedures under sedation. Methods PubMed, Medline, EMBASE, Cochrane Central Register of Controlled Trials and Web of Science, were searched from inception to 31 July 2021. Only randomized clinical trials comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
1
20
1
Order By: Relevance
“…In contrast to previous SRs, our analysis showed HFNC did not reduce the overall incidence of hypoxemia [19][20][21]. This phenomenon could be explained by the different statistical models used by each SR, especially when the included studies had heterogenous study designs or zero events (i.e., zero incidence in one or both study group) [33].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In contrast to previous SRs, our analysis showed HFNC did not reduce the overall incidence of hypoxemia [19][20][21]. This phenomenon could be explained by the different statistical models used by each SR, especially when the included studies had heterogenous study designs or zero events (i.e., zero incidence in one or both study group) [33].…”
Section: Discussioncontrasting
confidence: 91%
“…However, the study designs were heterogeneous, and study results were inconsistent. Four recent systematic reviews (SRs) were published to demonstrate the benefit in use of HFNC for prevention of hypoxemia in patients who received GI endoscopies [19][20][21][22]. Based on the tool of "A Measurement Tool to Assess Systematic Reviews II" (AMSTAR2) [23], these SRs were appraised as critically low or of low quality, mainly due to lack of discussing the influence of RoB on the pooled estimates (Table A1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six systematic reviews have been published exploring the effects of HFNO during gastrointestinal, bronchoscopy and dental interventions [ 15 , 16 , 17 , 18 , 19 , 20 ]. Although these reviews were in favour of HFNO in mitigating the risk of hypoxaemia, there was a paucity of subgroup analyses exploring the influence of covariates and how it may influence the overall interpretation of data.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another systematic review also reported a lesser incidence of hypoxia (OR 0.02, 95% CI 0.00 to 0.07; heterogeneity I 2 = 39%) and airway interventions (OR 0.02, 95% CI 0.01 to 0.04; heterogeneity I 2 = 15%) with the use of high-flow nasal cannula in comparison to standard nasal cannula during digestive endoscopic procedures under sedation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%